A descriptive study on code-switching among grade 6 math and science teachers’ utterances - Mercado, Kathleen Ann A. (Animo Repository, 2010)
Code-switching (CS) is a linguistic phenomenon that bilinguals have the ability to execute. Its occurrence is almost always spontaneous, regardless of the context. While it is considered acceptable when used in informal settings, code-switching in a formal setting such as the classroom is often questioned. ESL/EFL teachers have found that code-switching serves different purposes in the language classroom that in turn helps learners understand lessons better. Apart from ESL/EFL classrooms, code-switching has also been analyzed as it occurs in content area classrooms. Having been considered a strategy to help students in the learning process in the language classroom, it seemingly serves the same purpose in Math and Science classrooms. The present study focuses on identifying classroom situations as defined by Arends (2000) whereby code-switching is said to occur. Furthermore, the present study provides a descriptive analysis of the types, strategies and functions of code-switching in Grade Six Math and Science teachers‟ classroom discourse. The study‟s findings reveal that intrasentential code-switching is the most dominant type of code-switching in Math and Science teachers‟ discourse, having occurred in all classroom situations. This may suggest that code-switching in the classroom may go as far as switching from one language to another within a sentence, an adherence to the conventional or seemingly fixed manner of code-switching. Smooth switching as a code-switching strategy is revealed to have occurred most frequently in the data analyzed as it was present in all situations. The dominance of smooth switching possibly indicates Filipino bilinguals‟ competency in being able to manipulate the syntax of both languages, enabling them to use them interchangeably. Finally, personalization/objectivization is found to be the most dominant function present in all vii classroom situations, possibly suggesting that code-switching is likely to occur when teachers are to give casual comments or restate facts discussed in class.